An efficient of estimation the load profile analysis of photo voltaic system with different shading of local city - Ali Sabri Allw; Ahmed Hussein Duhis; Ali Al-Ghanimi (Institute of Advanced Engineering and Science, 2022)
In this paper, we analysis the last technology of photovoltaic (PV) system and the main effective factors of operation in unique efficiency and optimize performance. the first of all we take the general view of physical aspects of sun light and motion of earth with respect of sun position, and analysis of light spectrum and its effect for each regen from spectrum on PV. We illustrated the results of variation of irradiance from deferent sites and show size system for same energy demand. We start by analysis of load-by-load profile working and go through to specify the economic azimuth degree and altitude degree depend on load profile and final put some technical suggestions to minimize the effect of shading and benefit from using a new technology by face shield (half cut cell). These calculations are proposed to make available well originated and equivalent important information so as to allow PV strategies to change quicker obsessed by arenas of application with different shading of local cityin AL-Mausaib Babylon, Iraq. The ratios of shading conditions (10%, 25%, 50%, 75%) and without shading were used as effectiveness restrictions. The outcomes confirmation that the performance of PV system is extensively reduced and the system can’t control the batteries, if the shading close 75% or additional for single panel.